2020 IEEE 21st International Workshop on Signal Processing Advances in Wireless Communications (SPAWC) 2020
DOI: 10.1109/spawc48557.2020.9154244
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Improvement in Wideband Reconfigurable Intelligent Surface-Aided Cell-Free Network

Abstract: Thanks to the strong ability against the inter-cell interference, cell-free network has been considered as a promising technique to improve the network capacity of future wireless systems. However, for further capacity enhancement, it requires to deploy more base stations (BSs) with high cost and power consumption. To address the issue, inspired by the recently proposed technique called reconfigurable intelligent surface (RIS), we propose the concept of RIS-aided cell-free network to improve the network capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 8 publications
0
44
0
Order By: Relevance
“…Let dBS,k, dBS,RIS, dRIS,k denote the distance between BS‐kth user, BS‐RIS and RIS‐kth user, respectively. Thus, the distance‐dependent path loss (PL) for the BS‐user link can be written as truerightPLfalse(dBS,kfalse)d=CdGBSGkdBS,kνBS,k,and the PL for the BS‐RIS‐user link can be written as PL(dBS,RIS,dRIS,k)r=CnormalrGBSGkdBS,RISνBS,RISdRIS,kνRIS,k,where Cd and Cr are the channel fading variables depending on the wavelength, channel status, and angle of departure (AoD); Moreover, Cr is also related to the angle of arrival (AoA), the material and size of RIS element [3]; GBS and Gk denote the antenna gain of the BS and the kth user; Here, we assume CnormaldGBSGk = −30 dB and CnormalrGBSGk = −40 dB [6]; The PL exponents for the BS‐RIS link and RI...…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Let dBS,k, dBS,RIS, dRIS,k denote the distance between BS‐kth user, BS‐RIS and RIS‐kth user, respectively. Thus, the distance‐dependent path loss (PL) for the BS‐user link can be written as truerightPLfalse(dBS,kfalse)d=CdGBSGkdBS,kνBS,k,and the PL for the BS‐RIS‐user link can be written as PL(dBS,RIS,dRIS,k)r=CnormalrGBSGkdBS,RISνBS,RISdRIS,kνRIS,k,where Cd and Cr are the channel fading variables depending on the wavelength, channel status, and angle of departure (AoD); Moreover, Cr is also related to the angle of arrival (AoA), the material and size of RIS element [3]; GBS and Gk denote the antenna gain of the BS and the kth user; Here, we assume CnormaldGBSGk = −30 dB and CnormalrGBSGk = −40 dB [6]; The PL exponents for the BS‐RIS link and RI...…”
Section: Simulation Resultsmentioning
confidence: 99%
“…From this figure, it is observed that as the horizontal distance D between the BS and users increases, the achievable spectral efficiency performance decreases rapidly due to the serious attenuation of the signals. However, a peak at D = 30 m indicates that the spectral efficiency of both PSO and existing scheme [6] increases when the users approach the RIS, since the users receive strong signals reflected from the RIS. On the other hand, no peak is observed for the conventional without RIS scheme.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of authors' knowledge, the RIS aided weighted sum rate (WSR) maximization problem for mmWave vehicular uplink is not investigated in the literature. Although, WSR maximization for RIS aided communication systems are investigated in [23], [24] and [25], those did not consider the vehicular scenario, and a continuous phase shift model is used for the RIS. WSR maximization for an RIS aided multiple-input single-output (MISO) downlink communication system is investigated in [25], where the authors use fractional programming (FP) techniques [26] to decompose the original problem into four disjoint blocks and to design a lowcomplexity algorithm based on the non-convex block coordinate descent (BCD) method.…”
Section: Introductionmentioning
confidence: 99%